Contact lens electroretinography in preterm infants from 32 weeks after conception: a development in current methodology. Issue 3 (1st May 2000) - Mactier, Helen; Hamilton, Ruth; Bradnam, Michael S; Turner, Thomas L; Dudgeon, John
Abstract : AIM: To assess the feasibility of using a contact lens electrode to record the electroretinogram (ERG) in preterm infants less than 35 weeks after conception. METHODS: The ERG was recorded from seven very low birthweight preterm infants on a total of 14 occasions using an infant monkey contact lens electrode. Age at recording the first ERG ranged from 23 to 51 days (gestational age 32–34 weeks), and weight ranged upwards from 1100 g. RESULTS: No complications were observed. With advancing age and maturity the dark adapted rod threshold decreased, indicating increased retinal sensitivity. CONCLUSIONS: Contact lens recording of the ERG from extremely small immature preterm infants is a practicable and well tolerated procedure. This method of recording the ERG will enable further evaluation of retinal development in this vulnerable population.